A two-stage parallel network DEA model for analyzing the operational capability of container terminals - PARK, Jaehun (Institutional Knowledge at Singapore Management University, 2020)
This study proposes a systematical approach to evaluate the operational capability of container terminals and discusses the effect of resource usages on operational performances. Two inter-dependent processes (i.e. the loading-discharging (L&D) and the delivery-receiving (D&R) operational processes) with shared/non-shared resources and common/separate productions are examined and characterized as a two-stage parallel network. An evaluation model is developed upon the principles of data envelopment analysis (DEA) to assess the operational capability of the terminals. Using the real-world dataset of 9 container terminals at Port of Busan, comparative performance results are obtained for 5 years spanning across 2014–2018. The proposed model demonstrates a much stronger discriminative power compared to the traditional CCR model in its estimations of performance in the decision-making units (DMUs). It can also be inferred from the results that efficiency in operations is a key qualifier for container volume while the market aggressiveness lends a competitive edge and reinforces a positive outcome on the performance of a container terminal. The study further examines the influence of management directive on a terminal performance and confirms that alignment of management directive with the operational capability of L&D and D&R processes is important in maximizing terminal throughout.